Effect of Treatment Delay, Stroke Type, and Thrombolysis on the Effect of Glyceryl Trinitrate, a Nitric Oxide Donor, on Outcome after Acute Stroke: A Systematic Review and Meta-Analysis of Individual Patient from Randomised Trials - Philip M. Bath; Lisa Woodhouse; Kailash Krishnan; Craig Anderson; Eivind Berge; Gary A. Ford; Thompson G. Robinson; Jeffrey L. Saver; Nikola Sprigg; Joanna M. Wardlaw; Blood pressure in Acute Stroke Collaboration (BASC) (Stroke Research and Treatment)
Background. Nitric oxide (NO) donors are a candidate treatment for acute stroke and two trials have suggested that they might improve outcome if administered within 4–6 hours of stroke onset. We assessed the safety and efficacy of NO donors using individual patient data (IPD) from completed trials. Methods. Randomised controlled trials of NO donors in patients with acute or subacute stroke were identified and IPD sought from the trialists. The effect of NO donor versus control on functional outcome was assessed using the modified Rankin scale (mRS) and death, by time to randomisation. Secondary outcomes included measures of disability, mood, and quality of life. Results. Five trials (4,197 participants) were identified, all involving glyceryl trinitrate (GTN). Compared with control, GTN lowered blood pressure by 7.4/3.3 mmHg. At day 90, GTN did not alter any clinical measures. However, in 312 patients randomised within 6 hours of stroke onset, GTN was associated with beneficial shifts in the mRS (odds ratio (OR) 0.52, 95% confidence interval (CI) 0.34–0.78) and reduced death (OR 0.32, 95% CI 0.14–0.78). Conclusions. NO donors do not alter outcome in patients with recent stroke. However, when administered within 6 hours, NO donors might improve outcomes in both ischaemic and haemorrhagic stroke.